Estimating nutrient stoichiometry and cascading influences on plankton in thermokarst lakes on the Qinghai-Tibet Plateau - Ze Ren; Jinlei Yu; Zhenmei Lin; Lixiang Zhang; Mei Wang (Communications Earth & Environment)
Abstract Thermokarst lakes play a critical role in global biogeochemistry. Here we delved into nutrient stoichiometry and its cascading effects on plankton communities across thermokarst lakes on the Qinghai-Tibet Plateau. Our findings revealed significant variability in nutrient concentrations and stoichiometric ratios in both water and seston, indicating heterogeneous nature of thermokarst lakes. Phytoplankton communities were dominated by cyanobacteria. Zooplankton communities, though simple, varied significantly and responded distinctly to the prevailing nutrient stoichiometry, and particularly shown competitive interactions between copepods and Cladocera. Structural Equation Modeling revealed a complex web of interactions, underscoring the bottom-up influences from nutrient stoichiometry in water to phytoplankton/seston, and finally to zooplankton, although there were no direct relationships between phytoplankton and zooplankton communities. Water nutrient stoichiometry positively affected eukaryotic algae but negatively impacted seston stoichiometry, which. had a negative influence on copepods. Our study highlighted the intertwined relationships between nutrient stoichiometry and plankton communities within thermokarst lakes.